Microsurgical denervation of rat spermatic cord: safety and efficacy data. (May 2014) - Laudano, Melissa A.; Osterberg, E. Charles; Sheth, Seema; Ramasamy, Ranjith; Sterling, Joshua; Mukherjee, Sushmita; Robinson, Brian D.; Parekattil, Sijo; Goldstein, Marc; Schlegel, Peter N.; Li, Philip S.
Abstract : Objective: To describe a microsurgical technique for denervation of the spermatic cord and use of multiphoton microscopy (MPM) laser to identify and ablate residual nerves after microsurgical denervation. To evaluate structural and functional changes in the rat testis and vas deferens after denervation. Materials and Methods: Nine Sprague‐Dawley rats were divided into three experimental groups: sham, microsurgical denervation of the spermatic cord (MDSC), and MDSC immediately followed by laser ablation with MPM. At 2 months after surgery, we assessed testicular volume, functional circulation of the testicular artery with Doppler, patency of the vas deferens, and histology of the testis and vas deferens. Results: There was a significant decrease in the median number of nerves remaining around the vas deferens with MDSC alone (3.5 nerves) or MDSC with MPM (1.5 nerves) compared with sham rats (15.5 nerves) ( P = 0.003). Although, MDSC with MPM resulted in the fewest remaining nerves, this result was similar to MDSC alone ( P = 0.29). No deleterious effects on spermatogenesis or vas patency were seen in the experimental groups when compared with the sham rats. Conclusion: A microsurgical approach can be used to effectively and safely denervate the rat spermatic cord with minimal changes to structure and function of the testis and vas deferens. MPM can be used as an adjunct to identify and ablate residual nerves after MDSC.